Cold atmospheric plasma decontamination of SARS‐CoV‐2 bioaerosols. Issue 3 (4th December 2021) - Bisag, Alina; Isabelli, Pasquale; Laghi, Giulia; Laurita, Romolo; Dirani, Giorgio; Taddei, Francesca; Bucci, Cristiana; Capelli, Filippo; Gherardi, Matteo; Paglianti, Alessandro; Sambri, Vittorio; Colombo, Vittorio
Abstract: Bioaerosols (aerosolized particles with biological origin) are strongly suspected to play a significant role in the transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2), especially in closed indoor environments. Thus, control technologies capable of effectively inactivating bioaerosols are urgently needed. In this regard, cold atmospheric pressure plasma (CAP) can represent a suitable option, thanks to its ability to produce reactive species, which can exert antimicrobial action. In this study, results; on the total inactivation of SARS‐CoV‐2 contained in bioaerosols treated using CAP generated in air are reported, demonstrating the possible use of CAP systems for the control of SARS‐CoV‐2 diffusion through bioaerosols. Abstract : A dielectric barrier discharge is used to directly inactivate bioaerosols containing SARS‐CoV‐2 flowing through it.